ANALISIS LINGUISTIK FORENSIK TERHADAP UJARAN KEBENCIAN NETIZEN PADA KOLOM KOMENTAR INSTAGRAM KAESANG PANAGREP DAN ERINA GUDONO TAHUN 2024 - Anggi Bela Komara; Aceng Hasani; Dodi Firmansyah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study uses a case study method with a qualitative approach. The objectives are to (1) describe the forms and meanings of hate speech by netizens in the comment sections of Kaesang Pangarep and Erina Gudono’s Instagram accounts in 2024, and (2) analyze the language units of hate speech in relation to legal provisions based on the Criminal Code (KUHP) and the Law of the Republic of Indonesia Number 19 of 2016 concerning Information and Electronic Transactions (UU ITE). The data sources are comments on the Instagram accounts of Kaesang and Erina that contain hate speech, as well as books, journals, and relevant studies to support the analysis. Data collection instruments include documentation through screen capture, literature review, reading, and note-taking. To ensure data validity, triangulation was used. This study examines linguistic features of hate speech in the Instagram comment sections of Kaesang Pangarep and Erina Gudono during August to October 2024 using a forensic linguistic approach. The analysis focuses on morphophonemic elements, syntactic units, lexical and grammatical meanings, and the context of utterances, offering a comprehensive linguistic perspective. The findings show that the forms of hate speech include insults, defamation, incitement, and the spread of false information. In terms of linguistic structure, the grammatical units found consist of words, phrases, clauses, and sentences. These elements reflect how hate speech is constructed and delivered in digital discourse. The results also demonstrate the relevance of forensic linguistic analysis in identifying potential legal violations related to language use in social media platforms.